2004
DOI: 10.1007/s00198-004-1709-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of height loss during prospective monitoring for detection of incident vertebral fractures

Abstract: Vertebral fractures are the most common type of osteoporotic fracture, but more than two-thirds remain undetected. We have examined the relationship between height loss and the development of new vertebral fractures to determine whether there is a height loss threshold that has useful clinical accuracy to detect new fractures. We studied 985 postmenopausal women with osteoporosis in the placebo arms of the Vertebral Efficacy with Risedronate Therapy studies. Height was measured annually for 3 years using a wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 17 publications
3
87
0
2
Order By: Relevance
“…(7,19,35) Treatment monitoring should also include assessment of possible adverse effects of therapy, interval fracture history, assessment of back pain, and body height measurement to determine whether VFA should be repeated. (36) There have been no analyses of the best frequency for reassessing fracture history, rescreening for vertebral fractures, or measuring height. Furthermore, the ideal interval for assessing BMD has not been studied and would depend on the difference between the patient's T-score and T-score goal and expected effects of the treatment.…”
Section: Monitoring Response To Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…(7,19,35) Treatment monitoring should also include assessment of possible adverse effects of therapy, interval fracture history, assessment of back pain, and body height measurement to determine whether VFA should be repeated. (36) There have been no analyses of the best frequency for reassessing fracture history, rescreening for vertebral fractures, or measuring height. Furthermore, the ideal interval for assessing BMD has not been studied and would depend on the difference between the patient's T-score and T-score goal and expected effects of the treatment.…”
Section: Monitoring Response To Therapymentioning
confidence: 99%
“…More than a 2 cm (>3/4 inch) decrease in measured height indicates an increased probability that a new vertebral fracture has occurred and warrants spine imaging with repeat VFA or radiography. (36,37) For the same reasons, if height and spine imaging were not obtained at baseline, they should be considered early during treatment. These principles are based primarily on expert opinion and warrant additional analysis of the cost and benefits of this approach.…”
Section: Monitoring Response To Therapymentioning
confidence: 99%
“…[50][51][52][53][54][55] Measurement of height loss is a good clinical indicator of vertebral fracture. 56 Klotzbuecher et al 57 performed a meta-analysis of the risk of future fracture, given the history of prior fracture, and concluded that women with prior fracture had a 2-to 10-fold risk of another fracture, compared with those without fracture. This risk was reported to further increase with the number of prior vertebral fractures.…”
Section: Women At Risk Of Fragility Fracturementioning
confidence: 99%
“…63 Postmenopausal women with historical height loss greater than 6 cm, prospective height loss greater than 2 cm, kyphosis, or acute incapacitating back pain syndrome should be sent for spine radiographs with specific request to rule out vertebral fractures. 56 …”
Section: Radiographsmentioning
confidence: 99%
“…(7,11,12) Kyphosis and height loss are thought to result mainly from underlying vertebral fractures, but have not yet gained much clinical interest other than as markers for osteoporosis. (13)(14)(15)(16)(17)(18) Height loss, however, not only could be caused by vertebral fracture, but also to some extent by intervertebral disk degeneration that decreases disk height; osteoarthritic conditions of the spine, hip, or knee, various inflammatory and structural/congenital spinal deformities; and weakness of the back muscles. (19,20) Our previous report showed that height loss and vertebral deformity significantly and independently affected quality of life (QOL) in the elderly, and height loss aggravated QOL more significantly than did vertebral deformity in all domains, even with different effect patterns between height loss and vertebral deformity.…”
Section: Introductionmentioning
confidence: 99%